LEGAL PROTECTION OF LECTURERS 'RIGHTS AND OBLIGATIONS AGAINST FOUNDATION INTERVENTION IN HIGHER EDUCATION - PERMAI YUDI; KRISTA SURBAKTI (CV KULTURA DIGITAL MEDIA, 2021)
Law no. 14/2005 on Teachers and Lecturers and Government Regulation of the Republic of Indonesia No. 37/2009 on Lecturers certainly guarantees the existence of lecturers in universities both public and Private, especially swata universities often face off between lecturers and college managers namely foundations. The Foundation as one of the institutions that has a license to establish and or manage high-profile institutions often ignores the rules that apply in accordance with the laws and regulations, sometimes the foundation of a college often intervenes in the policies that will be issued by the head of the college, often harming the lecturers who are based in the college, thus harming the rights of lecturers, and not keeping agreements or contact work towards permanent lecturers or non-permanent lecturers. To ensure legal protection for lecturers both permanent and non-permanent in universities managed by the Foundation, therefore there needs to be more in-depth research on the Legal Protection of Lecturers' Rights and Obligations against Foundation Intervention in Universities This research is a normative empirical juridical research, namely by conducting an analysis of the problem through studying the legal norms contained in the laws and regulations in Indonesia and looking at the reality that occurs in the field. How is it technically done in the field against the rights and obligations of lecturers to the intervention of the foundation, whether in accordance with the applicable laws in Indonesia. Whereas Law Number 14 of 2005 concerning Teachers and Lecturers only guarantees legal protection in carrying out professional duties, does not guarantee legal protection regarding the rights and obligations of a lecturer who receives a wage or salary from a tertiary institution, let alone the existence of a foundation intervention that manages a tertiary institution which is protected by Law No. 16 of 2001 concerning the Foundation. Thus, it is very necessary to have a new legal arrangement or legal product to regulate legal protection of the rights and obligations of lecturers, legal products can be in the form of Laws, Ministerial Regulations and Regional Regulations if it is possible that these regions have the same vision and mission government, namely the intellectual life of the nation one of the goals of the Republic of Indonesia.